PENINGKATAN MOTIVASI BELAJAR TEMA 1 INDAHNYA KEBERSAMAAN MELALUI MODEL PEMBELAJARAN GROUP INVESTIGATION PADA SISWA KELAS 4 SDN 1 SUKOREJO - Yossy Aprisita Putri; Henny Dewi Koeswanti; Sri Giarti (JURNAL TEMATIK, 2019)
This study aims to increase the motivation to learn theme 1 through the application of the Group Investigation learning model for 4th grade students of SDN 1 Sukorejo. This research is a Classroom Action Research (CAR) carried out in two cycles consisting of 4 stages, namely the stages of planning, implementation, observation, and reflection. The subjects of this study were students in grade 4 at SDN 1 Sukorejo, totaling 30 students. The data collection technique used was non-test (observation, documentation) and then analyzed descriptively quantitatively. The results showed an increase in the average percentage of learning motivation from the first cycle totaling 7 students (23.33%) included in the classification highly motivated, 11 students (36.67%) entered the classification quite motivated while 12 students (40%) entered in classification is not motivated and cycle II as many as 26 students (86.67%) enter the classification highly motivated and 4 students (13.33%) in the classification are quite motivated. Based on the results of the study it can be concluded that the Group Investigation learning model can increase motivation to learn theme 1 grade 4 SDN 1 Sukorejo.